2020
DOI: 10.1007/s12182-020-00442-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep-water depositional architecture and sedimentary evolution in the Rakhine Basin, northeast Bay of Bengal

Abstract: Since the consecutive discovery of several gas fields from 2004 to present, the Rakhine Basin has been an active area for petroleum exploration in the Bay of Bengal. High-resolution 3D seismic data and well data from blocks AD1, AD6 and AD8 offshore northwest Myanmar are used to study the Miocene-Pleistocene depositional architecture and sedimentary evolution in the Rakhine Basin. Analysis of seismic facies and seismic attributes indicates that deep-water architectural elements include submarine canyons, confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The large volumes of fine-grained sediments accumulate in high-relief levees that confine the flows, allowing flows to travel downslope for hundreds of kilometers. A similar association between high sediment supply, gentle slope gradient, and the occurrence of extensive channel-levee systems occurs in the convergent margin of India, along the Bengal fan (Ma et al, 2020). Also, large channel-levee systems have been documented in the salt-diapir-influenced Fuji-Einstein system (Eastern Gulf of Mexico, Milliman and Meade, 1983;Piper et al, 2012;Sylvester et al, 2012), in the extensional domain of the upper-and mid-slope regions of the deep-water Niger Delta (Chima et al, 2019;Jolly et al, 2017) and in the Amazon Fan, (Pirmez et al, 2000;Pirmez and Flood, 1995).…”
Section: Sediment Supplymentioning
confidence: 73%
“…The large volumes of fine-grained sediments accumulate in high-relief levees that confine the flows, allowing flows to travel downslope for hundreds of kilometers. A similar association between high sediment supply, gentle slope gradient, and the occurrence of extensive channel-levee systems occurs in the convergent margin of India, along the Bengal fan (Ma et al, 2020). Also, large channel-levee systems have been documented in the salt-diapir-influenced Fuji-Einstein system (Eastern Gulf of Mexico, Milliman and Meade, 1983;Piper et al, 2012;Sylvester et al, 2012), in the extensional domain of the upper-and mid-slope regions of the deep-water Niger Delta (Chima et al, 2019;Jolly et al, 2017) and in the Amazon Fan, (Pirmez et al, 2000;Pirmez and Flood, 1995).…”
Section: Sediment Supplymentioning
confidence: 73%
“…Based on an analysis of seismic facies and attributes, previous studies found that the architectural elements mainly consist of a confined slope channel complex system and an aggradational channel levee complex [35,36]. Some studies hypothesized results that the basin underwent a rapid progradation during the Oligocene-Middle/ Upper Miocene, a gradual retrogradation during the Middle/Upper Miocene-Early Pliocene, and a gradual progradation during the Early Pliocene-Pleistocene [36]. Basu et al [37] described the stratigraphic chart and structural trends in the Rakhine Basin.…”
Section: Geological Settingmentioning
confidence: 99%
“…Turbidite systems in Rakhine Basin have received considerable attention recently, due to the discovery of the commercial Shwe gas field in the Rakhine turbidite systems of Pliocene age (e.g., Yang and Kim 2014;Zhan et al 2019;Ma et al 2020). The recoverable gas reserves from the Shwe gas field were estimated to contain 4 trillion cubic feet of extremely dry gas (Yang and Kim 2014).…”
Section: Geological Settings and The Study Areamentioning
confidence: 99%
“…However, plan-view distribution patterns of sandy supercritical-flow deposits in net-depositional cyclic steps remain undocumented, due to a lack of 3D anatomy of net-depositional cyclic steps. Ma et al (2020) have suggested that high-amplitude events imaged as peak reflectors are seismic responses to low gamma vs. high resistivity well-log signatures away from the shale baseline, both of which are asymptomatic of sand-rich lithologies composed mainly of fine-grained sandstones and siltstones. High seismic amplitudes are high RMS attributes in the Bengal seismic database utilized in this study, therefore, represent seismic responses of sandy deposits.…”
Section: Conceptual Implicationsmentioning
confidence: 99%